Chronic cyanosis since infancy: Unveiling a giant right pulmonary arteriovenous malformation - Dian Komala; Harry Galuh Nugraha; Firman Ramadhan; Rais Khairuddin; Rahmat Budi Kuswiyanto; Putria Rayani Apandi (Radiology Case Reports)
Giant pulmonary arteriovenous malformations (PAVMs) are rare vascular anomalies involving direct connections between pulmonary arteries and veins, leading to right-to-left shunting and systemic hypoxemia. While small PAVMs may be asymptomatic, larger lesions often present with dyspnea, cyanosis, and related complications. An 18-year-old female with progressive dyspnea and cyanosis—first noted during infancy—was found to have a giant PAVM in the right lower lung lobe on thoracic computed tomography (CT). Imaging, particularly computed tomography (CT), was essential for diagnosis and treatment planning. This case underscores the need to consider PAVMs in the differential diagnosis of chronic cyanosis and highlights the critical role of radiologists in identifying and characterizing these lesions to guide appropriate management.and characterizing these lesions to support optimal clinical decision-making.